Edukasi Stop Bullying melalui Program KKN di SD Negeri 01 Banjaran - Nurmutakin, Adi Yusuf; Riffadilah, Dhefin Gifari; Yulianti, Elisa; Khalifah, Nina; Nurfirdaus, Nunu; Oktafiana, Rival; Ramadhan, Rizkyana Fadly; Oktaviana, Varel Lingga (Indo-MathEdu Intellectuals Journal, 2025)
Bullying is one of the most serious issues in primary education, negatively affecting students’ psychological well-being and academic performance. The Community Service Program (KKN) conducted by students of Universitas Muhammadiyah Kuningan in Banjaran Village, Salem District, Brebes Regency, implemented an educational activity entitled “Stop Bullying Education” for fifth-grade students at SD Negeri 01 Banjaran. This program aimed to improve students’ understanding of the forms, impacts, and prevention of bullying, as well as to foster respectful social interactions. Data were collected through observation, group discussions, interactive question-and-answer sessions, and documentation during the activity. The collected data were analyzed using a descriptive qualitative approach to identify changes in students’ knowledge and responses after participating in the program. The results indicated an increase in students’ comprehension of bullying concepts, its negative consequences for victims, and the importance of reporting bullying incidents to teachers. Furthermore, the program encouraged students to openly share their personal or witnessed experiences related to bullying. Thus, the Stop Bullying education program proved effective as a preventive effort to create a safe, inclusive, and conducive school environment for learning.